Der Gelehrte, der Schüler und ein Gimpelpaar: Ein vergessener griechischer Brief von Conrad Gessner an Johannes Pontisella III - Bernhard, Jan-Andrea (Zwingliana, 2021)
In the collection of funeral poems (epicedia) for Conrad Gessner published by Josias Simler in 1566 along with a biography of the deceased, two distichs stand out. They were penned by then 14-year-old Johannes Pontisella; one in Latin, one in Greek. An inconspicuous letter draft from Gessner to 12-year-old Pontisella in manuscript ZBZ Ms C 50a has recently been discovered to further document the relationship between Gessner and young Pontisella. This essay outlines the biography of Johannes Pontisella III. (1552–1622) and his family, who originated in the Val Bregaglia. It illustrates the friendship between Johannes Pontisella II. (ca. 1510–1574) and Gessner, which was based, among other things, on their common interest in botanical and zoological matters, as well as the relationship of Pontisella III. with Zurich’s scholarly society. It furthermore discusses the tradition of humanist Greek funeral poetry (epicedia) and epistolography of the time in general and for Gessner in particular, analyzing his letter to Pontisella III. on a linguistic level and within the context of education in the 16th-century Grisons. The description of “mountain bullfinches” in Gessner’s letter is discussed in the context of his ornithological studies. A bilingual, annotated edition of Pontisella’s epicedia and Gessner’s letter draft concludes the essay.